Humidification–Dehumidification (HDH) Desalination and Other Volume Reduction Techniques for Produced Water Treatment - Majeda Khraisheh (1349376) (2021)
Volume reduction has been suggested as a novel method to tackle the various challenges associated with produced water. The present solution offers an economical and environmentally friendly solution to treat a large bulk of produced water that may overwhelm conventional water treatment methods. The current study provides a review of the various volume reduction technologies including freeze concentration, reverse osmosis, and humidification and dehumidification desalination systems. Focus is concentrated on the general HDH technologies in addition to its integration with refrigeration cycles for conditioned air production, and the power cycles for power generation. The GOR, freshwater yield, and efficiencies of the integrated HDH systems were reviewed. Lastly, innovation in the HDH desalination technology is discussed with emphasis on its incorporation with the MVC process. Other Information Published in: Water License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/w14010060